The three trials of William Hone, for publishing three parodies . viz. The late John Wilkes's catechism, The political litany, and The sinecurist's creed; on three exofficio informations, at Guildhall, London, during three successive days, December 18, 19, & 20, 1817; before three special juries and Mr. Justice Abbott, on the first day, and Lord Chief Justice Ellenborough on the last two days.; (Hone, 1818)
The first trial of William Hone, [...]. 4th ed. 1817